Biomechanical and Perceived Comfort Analysis of FDM 3D-Printed Insoles for Flatfoot Treatment: A Systematic Literature Review - Lina Dianati Fathimahhayati; Ardiyanto Ardiyanto; Fitri Trapsilawati; Xiao Liu; Ali Zolfagharian; Herianto Herianto (Jurnal Optimasi Sistem Industri, 2025)
Flatfoot (pes planus), characterized by a reduced or absent medial arch, cause biomechanical disorders, pain and a risk of injury. Customized insoles are a key intervention, with the emergence of 3D printing fused deposition modelling (FDM) based on flexible materials such as thermoplastic polyurethane (TPU) and thermoplastic elastomer (THE). This systematic literature review, based on PRISMA guidelines and analysis of six Scopus studies, assesses the biomechanical and ergonomic properties of these insoles. The results show that flexible 3D printed inserts significantly improve biomechanics by increasing the height of the navicular arch, reducing excessive ankle joint eversion, increasing dorsiflexion and improving the distribution of plantar plate pressure. Regarding perceived comfort, evaluations using the Visual Analog Scale (VAS), the Likert scale and the American Orthopaedic Foot and Ankle Society (AOFAS) questionnaire consistently indicate improved user comfort over no insole or conventional option. Despite these advantages, challenges include limited material options, inconsistent print quality and technical fabrication problems. Further research is needed, especially large-scale studies, to resolve these problems and to improve the clinical use of the product. In conclusion, flexible inserts printed with FDM have the potential to improve both the biomechanical function and the perceived comfort of the footwear use.